(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
The study was attempted with an objective to check the purity of commonly used farmers rice seed stock. Assessment of varietal purity of collected 76 rice genotypes showed that there was a variation among the genotypes for varietal purity. Thirty-two genotypes showed 100% varietal purity and forty-four genotypes were contaminated with different types of offtypes. The lowest varietal purity was observed in Lal gotal (74.67%). Grain dimension and 1000 seed weight were measured as important physical characteristics of seed to identify varietal purity. Int. J. Agril. Res. Innov. & Tech. 5 (1): 15-21, June, 2015